Evaluation of levels of (VZV IgG, IL 21, IL - 23 and PLG) among patients with shingle in Thi-Qar Province - Ihsan Rashad Shaalan; Talib Hassan Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
With age, cell-mediated immunity is known to decrease as part of immunosenescence which renders old people more susceptible to cancer and previously encountered infectious diseases such as VZV, Eventually, older people are more susceptible to complications. This research reveals the level of interleukin profile (IL 21 and IL - 23) and assessed the level of VZV IgG antibodies and checking level PLG that reflect cell mediate and humoral immunities in patients with herpes zoster as an attempt to predict the complications of reactivation of the virus. According to the findings of this research, the titer of VZV IgG antibody and serum levels of cytokines IL-21 and IL-23 increased significantly in HZ patients compared to the control group, while HZ patients’ plasma plasminogen levels dropped in comparison to the control group.